The legislation of Ukraine and the Republic of Belarus about the normative legal acts: opportunities for improvement - Kosovych, Vitaliy M. (Journal of the Belarusian State University. Law, 2019)
The article is devoted to analysis of legal regulation of normative legal act status in the Republic of Belarus and in Ukraine. The focus is on the Law of the Republic of Belarus «About normative legal acts» and the draft of Law of Ukraine «About the regulatory legal acts». The author notes the similarity of these documents in the definition of «normative legal act», the legal formalization of rule-making technic and rule-making technology. Based on today doctrinal approaches, it is proposed to complement these documents by the norms, that stipulate during the regulations designing, rules of the usage of such funds of rule-making technics, as a legal structures, law principles, legal definitions, presumptions, fictions, postulates. The model of legal norm, that is devoted to legalize such a stage in the lawmaking process as legislative monitoring, is formulated.